2014
DOI: 10.1103/physreve.90.052145
|View full text |Cite
|
Sign up to set email alerts
|

Universal theory of efficiency fluctuations

Abstract: Using the fluctuation theorem supplemented with geometric arguments, we derive universal features of the (long-time) efficiency fluctuations for thermal and isothermal machines operating under steady or periodic driving, close or far from equilibrium. In particular, the probabilities for observing the reversible efficiency and the least likely efficiency are identical to those of the same machine working under the time-reversed driving. For time-symmetric drivings, this reversible and the least probable effici… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
194
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(206 citation statements)
references
References 44 publications
10
194
1
Order By: Relevance
“…In contrast to Refs. [45,46], the phase space is found to be continuous with infinite microstates, and it has been shown that the large deviation function does not follow the universal nature as mentioned in Refs. [45,46].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In contrast to Refs. [45,46], the phase space is found to be continuous with infinite microstates, and it has been shown that the large deviation function does not follow the universal nature as mentioned in Refs. [45,46].…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, the large deviation function has two extrema: a maximum corresponds to the most probable efficiency, and the minimum occurs at Carnot efficiency. In a similar context, Verley et al [46], found an efficient way to compute the large deviation function of stochastic efficiency using the cumulant generating function of entropy productions for a small engine with finite state space. This method was verified by considering an example of a stochastic engine made up of a system of two states where each of these states is coupled to a heat reservoir at a distinct temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of these variables yields the efficiency which is thus itself random variable. Large deviation form of the corresponding probability distribution exhibits the following universal features [40][41][42][43][44][45][46][47][48]: (i) the most probable value of efficiency corresponds to its traditional definition using averages of work and heat, (ii) in case of time-reversal symmetric driving the least probable value of efficiency equals to η C .…”
Section: Introductionmentioning
confidence: 99%
“…The non self-averaging nature of fluctuations in stochastic efficiency and other quantities requires detailed understanding of full probability distributions as opposed to the average behavior [41,42]. Large deviation properties of such distributions are recently under theoretical investigations [45,46,47,48,49,50,51]. Research on fluctuation relations for heat engines [52,53,54] are being pursued.…”
Section: Introductionmentioning
confidence: 99%
“…However, fluctuation theorems provide a bound on efficiency of an engine valid for any finite time cycle. Recently, novel theoretical approaches to capture the statistical properties of stochastic efficiency of micro heat engines and mesoscopic thermoelectric engines with broken time-reversal symmetry are being developed, particularly at long time limit [43,44], claiming universal properties of the large deviation function related to the statistics of stochastic efficiency. To our knowledge, so far, no such study exists for micro-refrigerators.…”
Section: Introductionmentioning
confidence: 99%